2003
DOI: 10.1515/arh-2003-0007
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Master Curves of Polymer Modified Asphalt from Three Different Geometries

Abstract: Polymer modified asphalt is an highly temperature sensitive material. To obtain the master curves of dynamic material functions, for this material, it is necessary to perform the testing over the temperature interval from -30˚C to at least 90˚C. Since in this temperature range the polymer modified asphalt undergoes the transition from a glass-like to a Newtonian-like material, the benefit of using three testing geometries is studied here. The geometries used were: torsion bar (for the low temperatures), plate-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 5 publications
0
12
0
3
Order By: Relevance
“…The work done by Dickinson and Witt (1974), Franceschini and Momo (1980), Anderson et al (1994), Cheung and Cebon (1997), Phillips (1999), Marasteanu and Anderson (2001), Pegoretti and Ricco (2001), Airey (2002Airey ( , 2003, Harvey and Cebon (2003), Polacco et al (2003Polacco et al ( , 2004aPolacco et al ( , 2004b and many others has concluded that viscoelastic asphalt materials can have thermo-rheologically simple behaviour in small strain deformations. This implies that dynamic stress-strain measurements under a given set of temperature and loading rate/frequency conditions can be used to predict properties under a different set of conditions.…”
Section: Time -Temperature Superposition Principlementioning
confidence: 98%
“…The work done by Dickinson and Witt (1974), Franceschini and Momo (1980), Anderson et al (1994), Cheung and Cebon (1997), Phillips (1999), Marasteanu and Anderson (2001), Pegoretti and Ricco (2001), Airey (2002Airey ( , 2003, Harvey and Cebon (2003), Polacco et al (2003Polacco et al ( , 2004aPolacco et al ( , 2004b and many others has concluded that viscoelastic asphalt materials can have thermo-rheologically simple behaviour in small strain deformations. This implies that dynamic stress-strain measurements under a given set of temperature and loading rate/frequency conditions can be used to predict properties under a different set of conditions.…”
Section: Time -Temperature Superposition Principlementioning
confidence: 98%
“…The approach used to solve this issue was to react a polymer with the bio-oil. A bitumen additive should improve binder properties at both low and high in-service temperatures [49]. Consequently, at high temperatures, it should be durable enough to resist loads from traffic, which may result into rutting or permanent deformation; and also at low pavement temperatures, it is expected to be flexible enough to avoid excessive thermal stresses.…”
Section: Significance Of Polymer Modifiersmentioning
confidence: 99%
“…The testing geometry (25 mm or 8 mm diameter plates with 1.00 mm or 2.00 mm testing gap) was selected according to the expected materials' stiffness (Airey, 2002;Polacco, Vacin, Biondi, Stastna, & Zanzotto, 2003). In any case, the specimens were squeezed out between the two plates, trimmed off using a hot spatula, then the gap was set as required in order to guarantee the correct geometry of each sample.…”
Section: Experimental Programmementioning
confidence: 99%